The influence of planetary engulfment on stellar rotation in metal-poor main-sequence stars - Oetjens, Annika; Carone, Ludmila; Bergemann, Maria; Serenelli, Aldo (Astronomy and astrophysics, 2020)
Context: The method of gyrochronology relates the age of its star to its rotation period. However, recent evidence of deviations from gyrochronology relations has been reported in the literature. Aims: We study the influence of tidal interaction between a star and its companion on the rotation velocity of the star to explain peculiar stellar rotation velocities. Methods: We followed the interaction of a star and its planet using a comprehensive numerical framework that combines tidal friction, magnetic braking, planet migration, and detailed stellar evolution models from the GARSTEC grid. We focus on close-in companions from 1 to 20 MJup orbiting low-mass (0.8 − 1 M⊙) main-sequence stars with a broad metallicity of [Fe/H] = − 1 up to solar. Results: Our simulations suggest that the dynamical interaction between a star and its companion can have different outcomes that depend on the initial semi-major axis and the mass of the planet, as well as on the mass and metallicity of its host star. In most cases, especially in the case of planet engulfment, we find a catastrophic increase in stellar rotation velocity from 1 kms−1 to over 40 kms−1 while the star is still on the main-sequence. The main prediction of our model is that low-mass main-sequence stars with abnormal rotation velocities should be more common at low-metallicity, as lower [Fe/H] favours faster planet engulfment, based on the assumption that the occurrence rate of close-in massive planets is similar at all metallicities. Conclusions: Our scenario explains peculiar rotation velocities of low-mass main-sequence stars by the tidal interaction between the star and its companion. Current observational samples are too narrow and incomplete, and, thus, they are not sufficient for our model to be tested.
Gesehen am 10.05.2021